2011
DOI: 10.17925/eoh.2011.07.01.63
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Thrombopoietin Receptor Agonists as a Novel Treatment for Immune Thrombocytopenia

Abstract: Primary immune thrombocytopenia (ITP), until recently referred to as idiopathic thrombocytopenic purpura (ITP), is an acquired autoimmune disorder defined by isolated thrombocytopenia (platelet count <100x 10 9 /l) and the exclusion of other causes of thrombocytopenia. 1 The clinical manifestations of ITP are highly variable and range from the completely asymptomatic patient to frank haemorrhage from any site, the most serious of which is intracranial. 2 Several matters in terms of the optimal treatment of adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…15,16,36,37 Despite the wide spectrum of conditions where eltrombopag has been used, little is known about the mechanisms of action of this drug on human HSCs. The results of our study demonstrated that eltrombopag promoted successful in vitro human cord and peripheral blood-derived HSCs differentiation towards the megakaryocytic lineage, as assessed by the maturation of high ploidy megakaryocytes expressing the lineage-speEx vivo inquiry on Eltrombopag mechanism of action haematologica | 2016; 101 (12) 1485 27,28 stimulated the activation of all the main biochemical pathways downstream of the c-Mpl receptor. This activation resulted in the expansion of fully differentiated megakaryocytes with an enhanced ability to extend long branched proplatelets.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…15,16,36,37 Despite the wide spectrum of conditions where eltrombopag has been used, little is known about the mechanisms of action of this drug on human HSCs. The results of our study demonstrated that eltrombopag promoted successful in vitro human cord and peripheral blood-derived HSCs differentiation towards the megakaryocytic lineage, as assessed by the maturation of high ploidy megakaryocytes expressing the lineage-speEx vivo inquiry on Eltrombopag mechanism of action haematologica | 2016; 101 (12) 1485 27,28 stimulated the activation of all the main biochemical pathways downstream of the c-Mpl receptor. This activation resulted in the expansion of fully differentiated megakaryocytes with an enhanced ability to extend long branched proplatelets.…”
Section: Discussionmentioning
confidence: 66%
“…[23][24][25] After 13 days of culture, 50 and 100 ng/ml of eltrombopag failed to promote megakaryocyte differentiation (data not shown). Conversely, when concentrations of eltrombopag, in the same range as those measured in the serum of healthy subjects during oral eltrombopag administration (C max 7-10 mg/ml), 27,28 were used in culture, megakaryocytes efficiently differentiated from their progenitors. Specifically, starting from 200 to 500 and 2000…”
Section: Eltrombopag Supports Full Megakaryocyte Differentiation and mentioning
confidence: 99%
“…Eltrombopag is a non-peptide thrombopoietin receptor agonist which is administered orally in tablet. In a preclinic study, eltrombopag stimulates megakaryocytes differentiation and proliferation by stimulation in thrombopoietin receptor and this drug is dose-dependant (Stasi et al, 2011). Mechanism action of eltrombopag to activate thrombopoietin receptor is different with romiplastim.…”
Section: Eltrombopagmentioning
confidence: 99%
“…In vitro study, antibody that attack platelet glycoprotein (GP) Ib-IX-V might cause thrombocytopenia via megakaryopoiesis inhibition and pro-thrombocytes formation. (Stasi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation